DNA-based identification and OspC serotyping in cultures of Borrelia burgdorferi s.l. isolated from ticks collected in the Moravia (Czech Republic) - Norek, Adam; Janda, Lubomír; Žákovská, Alena (Journal of vector ecology, 2016)
Two different genetic loci, flaB and ospC, were employed to assign genospecies and OspC phylogenetic type to 18 strains isolated from ticks collected in Pisárky, a suburban park in the city of Brno, Czech Republic. The RFLP analysis revealed three different genospecies (B. afzelii, B. garinii, and B. valaisiana). Three samples from the collection contained more than one genospecies. In the other 15 strains, nucleotide sequences of flaB and ospC were determined. The following phylogenetic analysis assigned 12 isolates to genospecies B. garinii and three to B. afzelii. These isolates were further subdivided into seven distinct ospC groups. The most related OspC types were G2, G4, and G5 (B. garinii) and A3 and A8 (B. afzelii).
Keywords: lymeská nemoc; Animals; Borrelia burgdorferi; antigeny bakteriální; klíště; proteiny vnější bakteriální membrány; polymorfismus délky restrikčních fragmentů; flagelin; DNA bakterií; Flagellin B; Serotyping; Bacterial Outer Membrane Proteins; DNA, Bacterial; Lyme disease; Borrelia burgdorferi komplex; Tick; Borrelia burgdorferi Group; Phylogeny; Polymorphism, Restriction Fragment Length; Czech Republic; Lyme Disease; Antigens, Bacterial; Česká republika; Flagellin; zvířata; fylogeneze; OspC; sérotypizace; Ixodes